The WFME global standards for quality improvement of postgraduate medical education: Which standards are also applicable in Germany? Recommendations for physicians with a license for postgraduate training and training agents - Schwill, Simon; Kadmon, Martina; Hahn, Eckhart Georg; Kunisch, Raphael; Berberat, Pascal O.; Fehr, Folkert; Hennel, Eva (GMS Journal for Medical Education, 2022)
Background: In Germany, the (model) regulation for postgraduate medical education 2018, the professional codes of conduct of the regional medical councils and the health professions chamber laws of the federal states are the formal basis of postgraduate medical education, but say little about its structure, processes and results. The World Federation for Medical Education (WFME) has developed global standards for improving the quality of postgraduate medical education and published them in a revised edition in 2015. A German version which takes the specifics of medical training in Germany into account has not been published to date. Objective: The Committee for Postgraduate Medical Education (PGME) of the Society for Medical Education (GMA) has set itself the goal of firstly translating the WFME standards into German and secondly making recommendations for physicians with a license for post-graduate training (PLT) and training agents (TA) in clinics and practices which have been adapted to the German context. Methods: The WFME standards were translated into German by a working group of the GMA Committee for PGME, the terminology adapted to PGME in Germany and checked by an interdisciplinary panel of experts made up of 9 members of the committee. In a second step, the WFME basic standards and quality standards for PGME relevant to PLTs and TAs in Germany were iteratively determined by this panel of experts using the Nominal Group Technique (NGT) and compiled in the form of recommendations. Results: The translation of the WFME guidelines was approved by the expert group without any changes to the content, taking into account the terminological system of PGME in Germany. In a second step, 90 standards were identified which were considered helpful for PGME in Germany, especially for PLTs and TAs (such as development of a professional identity, a more patient-centered approach or support of self-directed learning). Care was taken to only give recommendations which can be influenced by PLTs and TAs. These standards have been summarized as recommendations to PLTs and TAs and take into account all chapters of the WFME standards. Conclusion: The WFME standards selected here are recommended to PLTs and TAs in clinics and practices to achieve high-quality PGME. Empirical longitudinal studies will be required to examine both the implementation and the results of applying the modified WFME criteria in Germany.
CRIS-Team Scopus Importer:2022-10-07
Keywords: license for postgraduate training; lifelong learning; medical education; physicians with a license for postgraduate training; postgraduate medical education; postgraduate training center; quality assurance; WFME global standards for quality improvement of postgraduate